TRADITIONAL HERBAL BASED DISEASE TREATMENT IN SOME RURAL AREAS OF BANDIPORA DISTRICT OF JAMMU AND KASHMIR, INDIA - Lone, Parvaiz Ahmad; Bhardwaj, Ajay Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: Plants have been traditionally used for hundreds of years as a source of medicine by indigenous people of different ethnic groups inhabiting various terrains for the control of various ailments afflicting humans and their domestic animals. Today not only the medicinal plants but also their associated traditional knowledge is threatened due to a range of both natural and anthropogenic factors. In this backdrop, urgent ethnobotanical investigations and subsequent conservation measures are required to save these resources from further loss. Present study was designed with the sole purpose of eliciting the firsthand precious wealth of information on the traditional medicinal uses of plants practiced by the people residing in far flung and remote areas of the Bandipora district of Jammu and Kashmir, India. Methods: Frequent field trips and plant collections were made from various far flung and remote areas of the Bandipora district from March 2012 to September 2012. The district is floristically rich with sizable population of tribal communities and forest dwellers. Methods used to document the traditional knowledge included interviews and discussions with local knowledgeable persons, herbal healers called Bhorisâ€ and Tribals (Gujjars and Bakkerwals). Results: A total of 25 different plant species belonging to equal number of genera and 21 different families were found to be used as effective remedies by the local people in their day to day life to cure various human and livestock ailments. Angiosperms comprised the highest number (23 species) followed by one pteridophytic and one gymnospermic species. Conclusion: Traditional uses of medicinal plants against different ailments plays a significant role in meeting the primary health care needs of the local people especially rural communities of the study area. The information on traditional uses of plants could serve a useful source for pharmacologists, phytochemists, botanists and to those interested in the development of alternative therapies Keywords: Traditional knowledge, ailments, Bhoris, tribals, Bandipora.